2013
DOI: 10.5007/1980-0037.2013v15n6p705
|View full text |Cite
|
Sign up to set email alerts
|

Fatores influenciadores da ansiedade competitiva em atletas Brasileiros

Abstract: The study of factors influencing competitive anxiety, according to a multidimensional perspective and supported by valid instruments, is scarce among Brazilian athletes of different sports. The present study aims to: i) investigate the theoretical relationship between the different dimensions of the multidimensional theory of anxiety (i.e., cognitive anxiety, somatic anxiety and self-confidence); and ii) investigate the effects of gender, type of sport (individual or collective) and competitive experience leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
1
4
1
3
Order By: Relevance
“…The athletes in the intervention group (IG) showed higher cognitive anxiety levels than the athletes in the control group (CG). Considering that the IG athletes had more time as federated athletes and participated in more competitions than the CG, these results were contrary to research [ 37 , 38 ] that indicated that athletes with more competitive experience presented lower cognitive and somatic anxiety scores, compared to younger athletes with little competitive experience. On the other hand, other studies [ 34 , 39 ] found no statistically significant differences regarding competitive anxiety between younger, less experienced, athletes in a sport and more experienced athletes.…”
Section: Discussioncontrasting
confidence: 98%
“…The athletes in the intervention group (IG) showed higher cognitive anxiety levels than the athletes in the control group (CG). Considering that the IG athletes had more time as federated athletes and participated in more competitions than the CG, these results were contrary to research [ 37 , 38 ] that indicated that athletes with more competitive experience presented lower cognitive and somatic anxiety scores, compared to younger athletes with little competitive experience. On the other hand, other studies [ 34 , 39 ] found no statistically significant differences regarding competitive anxiety between younger, less experienced, athletes in a sport and more experienced athletes.…”
Section: Discussioncontrasting
confidence: 98%
“…The comparison of competitive anxiety of athletes according to sex showed differences for CA and SC, indicating that male athletes are more self-confident profile and felt less worried and showed less negative thoughts in moments before the competition. Our findings corroborate previous studies, such as Fernandes et al (2013) and Souza et al (2012), who pointed out higher CA scores for females. Coutinho, Giovanini, Pavini, Ventura, Elias and Silva (2015) affirm that women's emotional responses are more intense due to the biological and hormonal factors of the different phases of women's lives, such as hormonal regulation and the menstrual cycle, besides various social roles women have in the current society.…”
Section: Discussionsupporting
confidence: 93%
“…To measure these components, Martens, Burton, Vealey, Bump & Smith (1990b) developed the Competitive State Anxiety Inventory 2 (CSAI-2). Studies have shown that these dimensions of competitive anxiety tend to be influenced by variables such as gender, modality and level of skill and competitive experience (Woodman & Hardy, 2003;Fernandes, Nunes, Vasconcelos-Raposo & Fernandes, 2013;Teixeira, Nunes & Cruz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Corroborando o estudo anterior, Fernandes [16] revela que atletas do sexo feminino apresentaram maiores níveis de ansiedade e menores níveis de autoconfiança, enquanto atletas do sexo masculino apresentaram baixos níveis de ansiedade e níveis elevados de autoconfiança. O autor também relata que atletas de esportes individuais apresentaram menores níveis de ansiedade do que atletas de esportes coletivos, além disso, atletas com alta experiência possuem menores escores de ansiedade em comparação a atletas de baixa experiência, ou seja, quanto maior a experiência competitiva de um atleta, maior a sua autoconfiança.…”
Section: Discussionunclassified
“…No entanto, Sari [11] e De Pero [17] não partilham das mesmas conclusões de Judge et al [3] e Fernandes [16], pois os resultados apresentados pelos autores revelam que não há diferença significativa entre os gêneros. Para Sari [11], as variáveis analisadas foram a orientação da tarefa, orientação do ego, autoeficácia geral e a ansiedade traço entre os participantes (homens e mulheres) e, dentre todas não foram encontradas diferenças significativas entre os sexos.…”
Section: Discussionunclassified